Single Amino Acid Insertion in Loop 4 Confers Amphotropic Murine Leukemia Virus Receptor Function upon Murine Pit1 - Lundorf, Mikkel D. (American Society for Microbiology, 1998)
Pit1 is the human receptor for gibbon ape leukemia virus (GALV) and feline leukemia virus subgroup B (FeLV-B), while the related human protein Pit2 is a receptor for amphotropic murine leukemia virus (A-MuLV). The A-MuLV-related isolate 10A1 can utilize both Pit1 and Pit2 as receptors. A stretch of amino acids named region A was identified in Pit1 (residues 550 to 558 in loop 4) as critical for GALV and FeLV-B receptor function. We have here investigated the role of region A in A-MuLV and 10A1 entry. Insertion of a single amino acid in region A of mouse Pit1 resulted in a functional A-MuLV receptor, showing that region A plays a role in A-MuLV infection. Moreover, the downregulation of 10A1 receptor function by changes in region A of human Pit1 indicates that this region is also involved in 10A1 entry. Therefore, region A seems to play a role in infection by all viruses utilizing Pit1 and/or Pit2 as receptors.